ESTIMATION OF HEAT FLUX CAUSED BY SOLAR IRRADIATION ON A DRIVER OF PASSENGER CAR USING NUMERICAL SIMULATION - Ružić, Dragan; Stepanov, Borivoj (Journal of Applied Engineering Science, 2013)
In this paper, the influence of solar radiation direction and intensity on thermal flux on passenger vehicle driver's body was analysed. The analysis was carried out on a virtual model of a vehicle cabin. The results showed that the highest heat flux caused by solar radiation could occur when the sun is shining in the front of the vehicle, as proposed in standard ISO 14505-2: 2008. Under these conditions, driver's chest is the segment with the highest heat flux. The unfavourable situation due to highly asymmetric thermal condition is also when the sun is shining on the left side of the cabin. From that reason, paying attention to solar characteristics of glass and to design of air distribution system in such way that air-conditioner vents can be directed to areas with the highest fluxes is an efficient way to reduce the driver's and passenger's thermal stress.
Keywords: Thermal comfort; Automotive glass; Virtual thermal manikin; Solar radiation; Cabin